The Effect of Factors in Fraud Diamond Perspective on Fraudulent Financial Reporting - Inayanti, Shofia Nur; Sukirman, Sukirman (Accounting Analysis Journal, 2016)
Abstrak Laporan keuangan merupakan proses akhir di dalam suatu siklus akuntansi yang mencerminkan kondisi perusahaan di dalam suatu kurun waktu tertentu. Pada saat perusahaan menerbitkan laporan keuangannya, maka setiap perusahaan selalu dituntut untuk membuat laporan keuangan yang wajar dan menunjukkan kinerja manajeman yang baik. Dengan adanya tuntutan tersebut, dapat mendorong manajemen untuk melakukan tindakan kecurangan dengan memanipulasi laporan keuangan. Penelitian ini bertujuan untuk menganalisis pengaruh financial stability, personal financial need, nature of industry, multiple directorships of board members, change in auditor, rationalization, dan capability terhadap fraudulent financial reporting. Populasi dalam penelitian ini adalah perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia tahun 2011-2014 yang terdiri dari 130 perusahaan. Teknik pengambilan sampel adalah metode purposive sampling yang menghasilkan sampel sebanyak 38 perusahaan. Metode analisis data menggunakan analisis statistik deskriptif dan analisis regresi logistik. Hasil pengujian secara simultan menunjukan bahwa financial stability, personal financial need, nature of industry, multiple directorships of board members, change in auditor, rationalization, dan capability berpengaruh terhadap fraudulent financial reporting. Pengujian parsial menunjukan bahwa financial stability, nature of industry, dan rationalization berpengaruh positif terhadap fraudulent financial reporting. Sedangkan personal financial need, multiple directorships of board members, change in auditor, dan capability tidak berpengaruh terhadap fraudulent financial reporting. Abstract The financial report is final process in an accounting cycle represents the conditions of the companies within a certain period of time. When the companies published their financial report, every company is always demanded to make a fair financial report and showed a good performance management. The existence of these demand, could push management to make fraud by manipulating financial report. This study aims to give empirical evidence about the influence of financial stability, personal financial need, nature of industry, multiple directorships of board members, change in auditor, rationalization, and capability toward fraudulent financial reporting. The population in this study are the manufacturing companies listed in Indonesia Stock Exchange for year of 2011-2014 which consist of 130 companies. The sampling technique is a purposive sampling method which results for 38 samples. The data analysis method used descriptive statistic analysis and logistic regression analysis. The result of this study simultaneously shows that financial stability, personal financial need, nature of industry, multiple directorships of board members, change in auditor, rationalization, and capability give effects on fraudulent financial reporting. Partial test shows that financial stability, nature of industry, and rationalization give effects on fraudulent financial reporting, while personal financial need, multiple directorships of board members, change in auditor, and capability does not affect on fraudulent financial reporting.